PERAN PARALEGAL PASCA BERLAKUNYA PERMENKUMHAM NOMOR 3 TAHUN 2021 TENTANG PARALEGAL DALAM MEMBERIKAN BANTUAN HUKUM - Ade Saefudin (2022)
The high rate of poverty makes free legal aid very much needed by the community. Paralegals are one of the tools in distributing legal aid to the poor in Indonesia, but the role of paralegals is considered one-sided so that it is not known by many people, both about its definition, authority, and scope of work. Therefore, this study aims to answer the problem and to find out how the authority of paralegals according to permenkumham no. 3 of 2021 concerning paralegals in providing legal assistance and knowing how the urgency of the role of paralegals in providing legal assistance. This research uses a normative type of legal research (normative juridical). Based on the results of the study that regarding the position of paralegals has actually been mentioned in several laws and regulations in Indonesia, but specifically and in detail it is only regulated and only has formal legitimacy after being regulated in the regulation of the Minister of Law and Human Rights of the Minister of Law and Human Rights no. 3 of 2021 concerning paralegals in the provision of legal bans. The presence of paralegals who sincerely help provide legal aid services makes it easy for every access to justice for the lower class community to be wider.